THE ROLE OF THE RATIO OF TAURIN / ALANIN AS A PREDICTOR OF THE EFFICIENCY OF MEDICAMENTOUS CORRECTION OF CARDIAC RHYTHM DISORDERS IN POSTINFARCT PATIENTS WITH TYPE 2 DIABETES MELLITUS - Belikova, J. (The Ukrainian Scientific Medical Youth Journal, 2018)
The aim: Determine the predictor quality of the taurine / alanine ratio (Tau / Ala) in predicting the antiarrhythmic activity of taurine (TN) and meldonium (ME) in patients with post-infarction cardiosclerosis (PIC) and diabetes mellitus type 2 (T2DM). Materials and Methods 92 patients were examined with PICS and T2DM, which were divided into two groups: main (MG), (n = 62): 34 women and 28 men, the median age of the patients was 65.4 years (interquartile interval (II) – 61 -69 years), and the control group (CG) (n = 30): 17 women and 13 men, the median age – 64.6 years (II 64-67 years). CG patients took only basic therapy (BT) preparations of PICS and T2DM. In order to study the complex and isolated effect of TN and ME, the MG was divided into 3 subgroups (SG) in accordance with the additional treatment to BT. Amino acids and the ratios between them were determined. According to the results of Holter ECG monitoring (HECM), heart rate disorders (HRD) was evaluated. Results: It was revealed that the effectiveness of treatment depends (p <0.05 by the Chi-square criteria) on the chosen treatment method. It was established that the combined use of TN and ME in patients SG 3 leads to a pronounced decrease in ventricular arrhythmia (VE) compared with CG (p = 0.02). There were no statistically significant differences in the effectiveness of treatment in the MG subgroups between themselves, and SG 1 and SG 2 from the CG were not detected (p = 0.49, p = 0.47 and p = 0.64, respectively). Against the background of the treatment, a significant increase in Tau / Ala in all subgroups was recorded. Conclusion The use of ME and TN for 12 weeks in patients with PICS with T2DM has a positive effect on the HRD and AMA values of the blood spectrum. The serum Tau / Ala ratio is a highly sensitive and highly specific predictor of the response to the drug correction of HRV in patients with PICS and T2DM.